SHRINKAGE AND CREEP CHARACTERISTICS OF PALM KERNEL SHELL CONCRETE - ADETUKASI ADESOLA OLAYINKA; IKPONMWOSA EFE EWAEN (Journal of Engineering Studies and Research)
This research work evaluates the shrinkage and creep characteristics of concrete containing Palm Kernel Shell (PKS) as partial replacement of natural coarse aggregate. Concrete was mixed at 0.55 water-cement ratio, mix proportion of 1:1:2 and percentage replacement of natural aggregate with PKS at 0%, 25 % and 50%. The creep and shrinkage results of Palm Kernel Shell Concrete (PKSC), increased as the percentage content of PKS increased in the concrete. The maximum creep strain observed for normal concrete, 25 % and 50 % PKS content were 0.00018 mm/m, 0.00057 mm/m and 0.00094 mm/m respectively. The maximum total shrinkage strain recorded for 0%, 25% and 50 % PKS content was 0.00102 mm/m, 0.00183 mm/m and 0.00247 mm/m respectively.